The Perspective of the socio-political matrix and its transformations prior to the social outbreak: a proximity to the Chilean north (2016-2018) - Jiménez Palacios, Ricardo (2021)
This material shows the political characteristics of Chilean society during the three years prior to the outbreak of October 2019. To account for this situation we have considered a theoretical and methodological contribution. In the theoretical aspect, we have considered the concept of sociopolitical matrix (MSP) and its destructuring process since the last decades of the 20th century. As a methodological element we have considered the «Longitudinal Social Study of Chile» (ELSOC) and the evidence that allows us to account for the destructuring of the MSP during the years prior to the outbreak. Thus, far from considering it an unforeseeable situation, the outbreak was the result of the MSP's deregulation processes and the processes of subjectivation within the framework of neoliberalism. Finally, with the present material we intend to realize that the processes of destructuring of the MSP, as well as those of neoliberal subjectivation, must be substantially located in a territorial framework, for which we expose the particularities of this phenomenon in the northern region of Chile.